(untitled) (Swiss Medical Weekly, 2015)
Cystic fibrosis (CF) is one of the most common genetic disorders. Mutations of the cystic fibrosis transmembrane regulator causes dysfunction of epithelial membranes within the gastrointestinal and respiratory system. Patients with CF are known to be at risk for gastrointestinal malignancies, and lung transplantation further increases this risk. We report a case series of three CF patients who developed adenocarcinoma of the gastrointestinal tract in the posttransplant setting. One of these case histories describes a gastric cancer, which is a novel and to date unreported observation. These data emphasise the importance of checking CF patients for the development of abdominal complications following lung transplantation.